2000
DOI: 10.1111/j.1530-0277.2000.tb02032.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Motor and Cognitive Deficits in Detoxified Alcoholic Men

Abstract: The pattern of functional deficits implicates at least two principal neural systems: the cerebellar-frontal system and the corticocortical system between the prefrontal and parietal cortices. In addition, age and amount of alcohol consumption were better predictors of motor than cognitive impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
189
1
10

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(214 citation statements)
references
References 87 publications
14
189
1
10
Order By: Relevance
“…For example, various studies have observed fluency deficits in users of alcohol (Noël et al 2001), cannabis (Croft et al 2001), and MDMA (Bhattachary and Powell 2001;Fox et al 2001). Similarly, there is growing evidence of working memory deficits in users of alcohol (Sullivan et al 2000), cocaine (Goldstein et al 2004), opiates (Mintzer and Stitzer 2002), and MDMA (Gouzoulis-Mayfrank et al 2003;Wareing et al 2000). There is also a large amount of evidence about the existence of deficits in reasoning (especially in cocaine users) on tasks similar to the similarities subtest used in this study (Easton and Bauer 1996;Di Sclafani et al 2002;Gillen et al 1998).…”
Section: Igt Performancementioning
confidence: 80%
“…For example, various studies have observed fluency deficits in users of alcohol (Noël et al 2001), cannabis (Croft et al 2001), and MDMA (Bhattachary and Powell 2001;Fox et al 2001). Similarly, there is growing evidence of working memory deficits in users of alcohol (Sullivan et al 2000), cocaine (Goldstein et al 2004), opiates (Mintzer and Stitzer 2002), and MDMA (Gouzoulis-Mayfrank et al 2003;Wareing et al 2000). There is also a large amount of evidence about the existence of deficits in reasoning (especially in cocaine users) on tasks similar to the similarities subtest used in this study (Easton and Bauer 1996;Di Sclafani et al 2002;Gillen et al 1998).…”
Section: Igt Performancementioning
confidence: 80%
“…Typically, the processes affected are visuospatial abilities, executive functions, and gait and balance (for reviews, see Fein et al 1990;Moselhy et al 2001;Oscar-Berman 2000;Sullivan 2000), evidenced in both alcoholic men (Sullivan et al 2000d) and women (Sullivan et al 2002b). The executive functions affected include working memory, problem solving, temporal or- Fig.…”
Section: White Matter In Normal Aging and Alcoholismmentioning
confidence: 97%
“…For example, Melgaard et al (1990) and Volkow et al (1992) assessed chronic effects on rCBF and showed metabolic reversible decreases after detoxification (Volkow et al, 1994). There may be continuing effects on executive and visuospatial abilities, (Sullivan, Rosenbloom, & Pfefferbaum, 2000;Mann et al, 2001) (Bates et al, 1997), suggesting prefrontal and parietal damage, and stable over 21 days of treatment.…”
Section: Introductionmentioning
confidence: 92%